2016
DOI: 10.18632/oncotarget.8605
|View full text |Cite
|
Sign up to set email alerts
|

The DNA resection protein CtIP promotes mammary tumorigenesis

Abstract: Many DNA repair factors act to suppress tumor formation by preserving genomic stability. Similarly, the CtIP protein, which interacts with the BRCA1 tumor suppressor, is also thought to have tumor suppression activity. Through its role in DNA end resection, CtIP facilitates DNA double-strand break (DSB) repair by homologous recombination (DSBR-HR) and microhomology-mediated end joining (MMEJ). In addition, however, CtIP has also been implicated in the formation of aberrant chromosomal rearrangements in an MMEJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Murine studies have indicated that CtIP haploinsufficiency is tumor-promoting, whereas a complete loss of CtIP is detrimental, leading to inviability of mice (30). In contrast, murine tissuespecific conditional CtIP ablation systems indicated that a complete loss of CtIP suppresses tumorigenesis (31). However, it is likely that these observations are due to a deleterious decrease in cellular fitness linked to a complete loss of HRR.…”
Section: Discussionmentioning
confidence: 99%
“…Murine studies have indicated that CtIP haploinsufficiency is tumor-promoting, whereas a complete loss of CtIP is detrimental, leading to inviability of mice (30). In contrast, murine tissuespecific conditional CtIP ablation systems indicated that a complete loss of CtIP suppresses tumorigenesis (31). However, it is likely that these observations are due to a deleterious decrease in cellular fitness linked to a complete loss of HRR.…”
Section: Discussionmentioning
confidence: 99%
“…CtIP was originally reported as a tumor suppressor, partially due to its interaction with BRCA1 ( 62 , 63 ). However, a recent study suggested CtIP may facilitate mammary tumorigenesis in p53-deficient mice possibly through its function in MMEJ-mediated chromosome translocations and telomeric chromosomal fusions ( 64 ). In addition, Plk1 and Aurora A are frequently overexpressed in cancers including breast cancer ( 65–67 ).…”
Section: Discussionmentioning
confidence: 99%
“…On an organismal level, CtIP plays a role(s) in tumorigenesis, although what that role is, is not entirely clear. Thus, in one study CtIP haploinsufficiency was linked to significant tumorigenesis in mice but this was not confirmed in a similar subsequent study (25,26). However, genetic mutations of human CtIP have been linked to breast and ovarian cancer (27) supporting a role in tumor suppression.…”
Section: Introductionmentioning
confidence: 90%